Applying classical forest regulation methods to smallholdings with cooperative constraints - Rode, Rafael; Leite, Helio Garcia; Binoti, Daniel Henrique Breda; Ribeiro, Carlos Antonio Álvares Soares; Souza, Agostinho Lopes; Cosenza, Diogo Nepomuceno; Boechat, Carlos Pedro (CERNE, 2016)
This study aims to assess the cooperative regulation process of forestry producers in comparison to the traditional individual regulation of properties. Twenty (20) forest properties are studied as examples of the development of three forest regulation scenarios: 1) individual regulation, 2) group regulation, and 3) cooperative regulation. The Net Present Value (NPV) of each of the scenarios is optimized according to mathematical programming models and compared to a baseline scenario without forest regulation. According to the proposed cooperative regulation, properties had a proportion factor for annual net revenue distribution calculated from results of the baseline scenario. By comparing the NPV maximization results from scenarios 1 and 3 with the non-regulation scenario, the cost for individual regulation is on average 25%, while being only 11% for cooperative regulation, that is, a 14% reduction in property regulation costs. Additionally, cooperative regulation had the advantage of dividing properties into fewer areas when compared to individual regulation.

Este estudo teve como objetivo avaliar um processo de regulação cooperativa de produtores florestais, em comparar com o método de regulação clássico e individual das propriedades. Vinte propriedades florestais foram utilizadas 20 propriedades florestais como exemplo para elaboração de três cenários de regulação florestal: 1) regulação individual, 2) regulação em grupo, e 3) regulação cooperativa. O Valor Presente Líquido (VPL) dos cenários foram otimizados a partir de modelos de programação matemática, e comparados com um cenário base, sem regulação florestal. Para a regulação cooperativa proposta, as propriedades tiveram um fator de proporção para distribuição da renda líquida anual, calculado a partir do resultado do cenário base. Comparando os resultados da maximização do VPL dos cenários 1 e 3 com o cenário sem regulação, o custo da regulação individual foi, em média, de 25%, enquanto que para regulação cooperativa foi de 11%, ou seja, redução 14% no custo da regulação das propriedades. A regulação cooperativa apresentou ainda a vantagem de menor divisão das áreas das propriedades quando comparado à regulação individual.
Keywords: Forest management; Forest optimization; Rural properties; Forest owner